Sharia Compliance and Word-of-Mouth Strategy Effects on Customer Trust in Islamic Finance - Dwi Syahputra; Mutiah Khaira Sihotang (International Journal of Multidisciplinary Research of Higher Education, 2026)
Customer trust is a strategic asset for Islamic financial institutions in increasingly competitive markets. Sustaining this trust requires consistent adherence to Sharia principles and effective communication strategies, particularly through word-of-mouth. This study investigates the influence of Sharia compliance and word-of-mouth strategy on customer trust in Islamic financial institutions. A quantitative research design was employed, involving a survey of 98 customers selected through purposive sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression after fulfilling classical assumption tests, including validity, reliability, normality, multicollinearity, and heteroscedasticity. The findings reveal that Sharia compliance has a positive and significant effect on customer trust (β = 0.477, t = 4.986, p < 0.001), while word-of-mouth strategy also exerts a positive and significant effect (β = 0.414, t = 4.715, p < 0.001). Simultaneously, both variables significantly influence customer trust (F = 211.439, p < 0.001), explaining 90.5% of the variance (R² = 0.905). These results imply that strengthening Sharia governance and fostering positive customer experiences through word-of-mouth can substantially enhance trust, thereby reinforcing the long-term competitiveness and sustainability of Islamic financial institutions.